SOCIO-ECONOMIC FACTORS AFFECTING THE REDUCTION OF POVERTY IN INDONESIA IN ISLAMIC PERSPECTIVE - Tatik mariyanti (Business and Entrepreneurial Review, 2011)
In a developing country poverty reduction programs has become the center of attention in policy at national and at international agencies and institutions. This study aims to analyze the socioeconomic factors that affect poverty reduction in the perspective of Islam in Indonesia in 1994 until 2009, the data used in this study is time series data, using the variable as a determining factor of poverty in Indonesia is economic growth, the proportion of the population informal working sector, the proportion of population consuming malnutrition, the proportion of secondary-educated population down, unemployment, investment, government policy in the form of subsidies which are: subsidy funds derived from IDT, P2KP, PNP, Independent, PPIP, in addition to data from the BMT form of funding given to the poor, as well as data zakat alms per person infak poor. Analysis tools used in this study is to use a simultaneous equation modelanalysis using the software Eviews-4. From the analysis it can be concluded that all variables are seen in this study a significant influence on poverty reduction in Indonesia in 1994 until 2009, but subsidies and Islam is very small variable effect on poverty reduction in Indonesia.Recommendation of this study is the government should help in terms of funding for development of SMEs due to the Islamic microfinance institutions in effect, reduce poverty, and economic growth can reduce poverty is economic growth and equitable quality, investment as a contributor to economic growth must be done in the form of accelerated industrialization, the accumulation ofhuman capital in the form of education, as well as development and infrastructure improvements throughout the country. With the Islamic instruments namely zakat alms infaq very influential on poverty reduction while very little influence, because in Indonesia the role of zakat institutions have not been efficient because more people believe in giving alms alms infaq directly to the poor or the foundation that manages the orphans, but if domestic policy makers This would seriously to gradually use the instruments of Islamic finance as an instrument of poverty reduction, the authors believe poverty alleviation will be accelerated as well. Our nation will have economic independence, sovereignty and dignity so that the State can be maintained.